Post Option B+ implementation programme in Nigeria: Determinants of adherence of antiretroviral therapy among pregnant women with HIV. (April 2019) - Omonaiye, Olumuyiwa; Kusljic, Snezana; Nicholson, Pat; Mohebbi, Mohammadreza; Manias, Elizabeth
Highlights: Of surveyed pregnant women in Nigeria, about one-third self-reported taking all their ART doses in the past 96 h. Disclosure of HIV status to anyone was associated with ART adherence during pregnancy. Among pregnant women, previous prevention of MTCT was associated with ART adherence. An increased level of education among pregnant women was associated with ART adherence. Abstract: Objective: Nigeria has the highest rate of mother to child transmission of HIV (MTCT) in the world. By 2015, all Global Plan priority countries, except Nigeria, had adopted the Option B+ programme. Nigeria finally adopted Option B+ in 2016 with full implementation reported in 2017. We examined adherence to antiretroviral therapy (ART) among pregnant women since the rollout of Option B+ in Nigeria. Methods: A cross sectional approach was adopted that involved dissemination of a survey (Adult AIDS Clinical Trial Groups [AACTG] standardised survey) to HIV positive pregnant women, to assess adherence to ART. This study was conducted from February to June, 2018 in four health care sites in Akwa Ibom State, in the South-South region of Nigeria. Bootstrapping was used to estimate the 95% confidence interval of the prevalence of adherence. Bivariate associations between patient demographic characteristics and medication taking behaviours, and the outcome variable of ART adherence were examined using Chi-square tests. Multivariable logistic regression was used to identify factors independently associated with adherence. Results: Of the 275 women (response rate = 92.6%), 32.7% (95% CI: 26.9–38.5) self-reported taking all ART doses in the past 96 hours. In the multivariable logistic regression analyses, there were positive associations between an increased education level (OR = 1.7, p = 0.006) and disclosure of HIV status (OR = 2.3, p = 0.024), and medication adherence. For women who had previous prevention of MTCT exposure, the odds of medication adherence were 2.5 times higher compared with those with no previous MTCT exposure (OR = 2.5, p = 0.005). Conclusion: Adherence to ART among pregnant women in Nigeria is low. There is a need to improve adherence during pregnancy under the Option B+ programme in Nigeria.